The possibility of occurrence of chaotic modes of operation of electrical system with distributed generation - G. A. Koshuk; B. A. Kosarev; V. K. Fedorov; A. A. Okhotnikov (Омский научный вестник)
Possibility of origin of chaotic vibrations is in-process shown in the electrical engineering system with the up-diffused generation. Chaotic vibrations are malfunction of functioning of the electrosystems. Thus, from the point of view of the up-diffused generation the question of origin of chaotic office hours appears is worked out not enough. Therefore, the aim hired is consideration of possibility of origin of chaotic vibrations in the system with the up-diffused generation. The aim is arrived at by description of types of the set modes of operations of the system with the updiffused generation, reasons of origin and methods of stabilizing of chaotic vibrations.